The Effects of Military Knowledge, Family Support, and Media Exposure on Motivation to Pursue a Career in the Indonesian Navy: The Mediating Role of Military Professional Attitudes (Evidence from Generation Z Students at Hang Tuah Senior High School, Jaka - Fadillah, Suzan Noer; Sigit, Ridzki Rinanto (Journal of Industrial Engineering & Management Research, 2026)
This study examines the effects of military knowledge, family support, and media exposure on students’ motivation to pursue a career in the Indonesian Navy, with military professional attitudes as a mediating variable, focusing on Generation Z students at Hang Tuah Senior High School in Jakarta. Using a quantitative survey design, data were collected from 212 students through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that military knowledge, family support, and media exposure have positive and significant direct effects on students’ motivation to become Indonesian Navy personnel and also significantly influence their military professional attitudes. Furthermore, military professional attitudes play a crucial mediating role in strengthening the indirect effects of military knowledge, family support, and media exposure on motivation. These findings suggest that motivation to pursue a military career among Generation Z students is shaped not only by cognitive understanding and external social influences but also by the development of positive attitudes toward military values, roles, and professional identity. This study contributes to the literature by integrating motivational theory, social learning theory, social support theory, cultivation theory, and the theory of planned behavior into a comprehensive explanatory model. Practically, the findings highlight the importance of early military education, active family involvement, and positive media representation in fostering favorable attitudes and strengthening motivation among prospective candidates for the Indonesian Navy.